Mitigation of the Confirmation Bias Using a Game-Based Trainer. (September 2013) - Mersch, Elizabeth; Fox, Olivia; Leonard, Jim; Flach, John; Bennett, Kevin; Holt, Jerred
A search task was developed to test for confirmation bias in a virtual game-based trainer. The goal of the study was to test the effectiveness of the task in detecting analyst biases within the dynamics of virtual game-based trainers. In-game action and performance were measured. Results indicated that participants initially commit confirmation bias and then learn to mitigate it. Findings also show that participants understood the task and were engaged.